Effects of gut microbiota dysbiosis on the metabolism and pharmacokinetics of losartan in rats: from endogenous to ceftriaxone-induced dysbiosis - Xia, Jiaxuan; Jin, Yibao; Hong, Yanjun; Zhang, Yuefeng; Li, Meifang; Huang, Houshuang; Cai, Xu; Li, Dan; Wang, Bing; Xie, Zhiyong (Frontiers in Microbiology, 2025)
IntroductionGut microbiota plays a key role in drug metabolism. While gut microbiota dysbiosis is known to contribute to hypertension pathogenesis, its impact on drug metabolism remains poorly considered. Clinically, the pharmacokinetic variability of losartan potassium is partially attributed to genetic polymorphisms of the CYP2C9 enzyme and structural variations in AGTR1. However, the potential role of gut microbiota dysbiosis in regulating losartan pharmacokinetics remains unclear.MethodsIn the present study, we assessed the effect of gut microbiota dysbiosis on the metabolism and pharmacokinetics of losartan in two different rat models: spontaneously hypertensive rats (SHRs) with endogenous gut microbiota dysbiosis and rats with ceftriaxone (CRO)-induced gut microbiota dysbiosis combined with in vitro and in vivo studies.ResultsThe results showed that the intestinal flora from SHRs led to a more significant degradation of losartan than that from Wistar Kyoto rats (WKYs) in vitro. More importantly, we observed a reduction in the oral bioavailability of losartan in rats with gut microbiota dysbiosis. Specifically, compared to WKYs, the AUC0-∞ of losartan and its active metabolite E-3174 decreased by 50.24% (p < 0.05) and 72.42% (p < 0.01), respectively, in SHRs. In the WKY + CRO group, losartan AUC0-t decreased by 25.90% (p < 0.05) compared to WKYs; while the SHR + CRO group showed a 57.20% (p < 0.01) reduction compared to SHRs. Spearman correlation analysis of 16S rRNA full-length sequencing and pharmacokinetic parameters showed a significant negative correlation between Enterococcus faecalis (E. faecalis) abundance and losartan’s AUC0-t and Cmax. In vitro experiments concluded that E. faecalis metabolized losartan and converted it into E-3179. The reduced oral bioavailability of losartan in rats with CRO-induced dysbiosis was likely due to the effect of E. faecalis in degrading losartan.ConclusionThis study highlights that gut microbiota dysbiosis diminishes losartan bioavailability, providing evidence that gut microbiota contributes to the pharmacokinetic variability of losartan.